Generation of flood map using infoworks for Sungai Johor - Amin, Noor Farahain Muhammad; Othman, Faridah (Penerbit UTHM, 2018)
Flood has become regular disaster in Malaysia which it is happens every year in different states especially during northeast monsoon. Johor State, the most southern part of Peninsular Malaysia experienced numerous flooding from 1926 to 2013. However, Sungai Johor catchment had the most devastating impact during December 2006 and January 2007 flood events. The objectives of this study are to perform river modeling and generate a flood map fpr Sungai Johor. The river modeling of Sungai Johor has been done using InfoWorks RS software. Necessary data were collected and transferred into the required modelling procedures. The results indicated that the model was able to simulate the flood depth to a reasonable agreement and generate the flood map. The generated flood map can serve as a beneficial planning and design tools for the local authority and community in minimizing the flood effects and damage as well as in preparing the evaluation plan.